MUC1‐ and Survivin‐based DNA Vaccine Combining Immunoadjuvants CpG and interleukin‐2 in a Bicistronic Expression Plasmid Generates Specific Immune Responses and Antitumour Effects in a Murine Colorectal Carcinoma Model. (25th January 2018) - Liu, C.; Xie, Y.; Sun, B.; Geng, F.; Zhang, F.; Guo, Q.; Wu, H.; Yu, B.; Wu, J.; Yu, X.; Kong, W.; Zhang, H.
Abstract: DNA vaccination is a promising cancer treatment due to its safety, but poor immunogenicity limits its application. However, immunoadjuvants, heterogeneous prime‐boost strategies and combination with conventional treatments can be used to improve the antitumour immune effects. A CpG motif and interleukin‐2 (IL‐2) cytokine are often used as adjuvants. In this study, a DNA vaccine containing a CpG motif was constructed to evaluate its adjuvant effect. The results show that the cytotoxicity of the DNA vaccine was increased fivefold, and survival lifetime was prolonged twofold by the CpG motif adjuvant. To simplify the industrial production process, a bicistronic plasmid was constructed to carry the fusion genes of survivin/MUC1 (MS) and IL‐2 and with a CpG motif in its backbone. The results showed that the antitumour effect of the bicistronic vaccine was the same as that of the two vaccine co‐injected regime. Furthermore, the vaccine could suppress metastatic tumour foci by 69.1% in colorectal carcinoma‐bearing mice. Moreover, the vaccine induced survivin‐ and MUC1‐specific immune responses in splenocytes and induced the immune promoting factor CCL‐19 and GM‐CSF upregulated, while metastatic‐associated factor MMP‐9 and immunosuppressing factor PD‐L1 downregulated in tumour tissue. When combining the vaccine with the chemotherapy drug oxaliplatin, the survival was prolonged by about 2.5‐fold. In conclusion, the DNA vaccine containing a CpG motif in bicistronic form showed good effects on colorectal cancer by inhibiting both tumour growth and metastasis, and combination with oxaliplatin could improve its antitumour effects.